PENGGUNAAN MEDIA DALAM PEMBELAJARAN SEJARAH SMA DI KABUPATEN SEMARANG TAHUN AJARAN 2014/ 2015 - Alvionita, Heni (Indonesian Journal of History Education, 2015)
This study aims to determine the instructional media used by teachers, the constraints experienced by teachers in the use of media, and solutions to overcome the constraints experienced by teachers in the use of media pembelajaran.penelitian took place in Semarang District high school using interviews, observation, and documentation. The results showed that the medium used including LCD, maps, globes, documentaries, instructional CDs, pictures of figures, books, internet, and so forth. Constraints experienced teachers in the use of instructional media history that implement Curriculum SBC is a teacher lacking maximize the media that has been available as school facilities and teachers creativity in innovative learning media less, while obstacles encountered teachers in the use of instructional media in schools which implement Curriculum 2013 not too specific, just that it is conditional obstacle course. Â